Diffusion-weighted whole-body MRI for evaluation of early response in multiple myeloma. Issue 10 (October 2017) - Lacognata, C.; Crimì, F.; Guolo, A.; Varin, C.; De March, E.; Vio, S.; Ponzoni, A.; Barilà, G.; Lico, A.; Branca, A.; De Biasi, E.; Gherlinzoni, F.; et al.
Abstract : Aim: To evaluate the modifications of the apparent diffusion coefficient (ADC) in myelomatous lesions before and after induction treatment and the correlation with patient response to therapy according to International Myeloma Working Group (IMWG) criteria. Materials and methods: A homogeneous group of 18 patients with a diagnosis of symptomatic multiple myeloma who underwent whole-body MRI with diffusion-weighted imaging (DWI-MRI) before and after bortezomib-based induction chemotherapy were evaluated prospectively. Quantitative analysis of ADC maps of myelomatous lesions was performed with the following pattern types: focal pattern, diffuse pattern (moderate and severe), and "salt and pepper" pattern. Lesions were evaluated by quantitative image analysis including measurement of the mean ADC in three measurements. Imaging results were compared to laboratory results as the clinical reference standard. Results: A statistically significant increase in ADC values were found in the lesions of patients that responded to treatment. Interestingly, focal lesions showed a strongly significant increase in ADC values in responders, whereas no significant variation in ADC value in non-focal lesions (diffuse pattern and "salt and peppers" pattern) between responders and non-responders group was demonstrated. Conclusions: DWI-MRI could provide additional quantitative information useful in monitoring early therapy response according to ADC changes of focal lesions. Highlights: DWI-MRI can be used for assessing early response to therapy in Multiple Myeloma (MM). Quantitative measurement of ADC could be used as a bio-marker of treatment response in MM patients affected by focal lesions. DWI-MRI could open new scenarios in the selection of MM patients who might potentially benefit from different therapies.